Fracture mechanism and separation conditions of pineapple fruit-stem and calibration of physical characteristic parameters - Li, Mutong; He, Lin; Yue, Dandan; Wang, Binbin; Li, Junlue (International Journal of Agricultural and Biological Engineering, 2023)
At present, the research on the physical composition and properties of pineapple plants is scarce, and the uncertainty of fruit picking method is the key bottleneck factor hindering the research and development of pineapple harvesting machinery. Based on the statistics of survey data from many places, this paper analyzes the fruit-stem fracture mechanism and the theoretical conditions for optimal separation through structural modeling, mechanical behavior analysis and function judgment. On this basis, the "pineapple plant fixation bench" and "fruit-stem bending separation torque test equipment" were developed, and large-size, small-size tests and random optimization tests were carried out successively. The test results showed that the larger of the stem-stalk fixation distance, the more torque and fracture starting angle required for fruit fracture would increase, and the change range was small when the stem-stalk fixation distance was within 50 mm, and the probability of brittle fracture and complete separation was very high. When the space between the fracture section and the fruit-stem connecting point is about 5mm, the range of bending moment value required for the fruit-stem fracture is 1.88 to 2.77 N•m, the range of fracture starting angle is 12.2° to 18.1°, and the angular travel range during the separation process is 82.9° to 87.5°. When the stem-stalk fixation distance is about 15 mm, it is the best fruit-stem separation condition and the breaking torque measured in the verification test is about 2.76 N•m. The fracture starting angle is about 13.8°, the maximum prediction error is 13.1%, and the elastic modulus near the fruit-stem joint ranges from 16.1 to 23.9 MPa. This conclusion can provide an important design basis for the research and development of pineapple field picking robot and harvesting equipment.Keywords: pineapple harvesting; fracture mechanism of fruit and stem; separation conditions; experiment design; reverse calibrationDOI: 10.25165/j.ijabe.20231605.8079Citation: Li M T, He L, Yue D D, Wang B B, Li J L. Fracture mechanism and separation conditions of pineapple fruit-stem and calibration of physical characteristic parameters. Int J Agric & Biol Eng, 2023; 16(5): 248–259.